A Critically Compassionate Approach to Financial Literacy: A Pursuit of Moral Spirit - Thomas Lucey (MDPI AG, 2018)
An alternative perspective of financial literacy questioned the conceptual legitimacy of sustained personal fulfillment through maximization of financial net worth. In this alternative view, a focus on financial assets and their accumulation constitutes an activity of objectification that perceives other individuals as vehicles for personal social advancement, rather than stories or narratives of themselves. This paper argues that a critically compassionate approach to financial literacy represents a moral pursuit. It begins with the claim that human nature is both controlling and compassionate, and that this dual nature informs about the meaning of financial literacy. From this position, it considers what it may mean to be moral in this context and extending that conception to understandings of financial practice. Finally, it asserts broadening interpretations of financial literacy to include compassionate practices represent a moral consideration.